Pendampingan Teknis Dalam Analisa Timbulan Limbah Medis Padat Pada Rumah Sakit SMS Berjaya Kabupaten Kolaka - Buttomi Masgode, Muhammad; Puspaningtyas, Retno; Rustan, Fathur Rahman; Prasetyo, Bagus Eko; Dirgantara, Arya; La Ola, Mursalim Ninoy; Hidayat, Arman; Mansyur, Mansyur; Purnama, Haerul; La Ode, Al Tafakur (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2023)
Medical waste is produced in hospitals by a variety of means, including solid waste, gas, and liquid. Therefore, it is necessary to support the analysis of the production of solid medical waste at RS SMS Berjaya District of Kolaka. The purpose of this technical support is to find out the monthly quantity of solid medical waste as well as the solid medical waste disposal system carried out at SMS Berjaya Hospital. Use both qualitative and quantitative descriptions. The accompanying results showed that the solid medical waste produced from medical activities in each room during the observation was a source of non-acute infectious garbage. Class II and III hospital facilities produce the highest percentage of medical garbage 23.13 kg/day (46.26%), and the smallest unit of medical waste in each room is 2.59 kg/ day (5.18%). And in the Infectious Object Garbage, the largest in Class II & III facilities is 1.32 kg/day (29,53%). And Nifas/Perinatology facilities are much smaller than 0.4kg/day (8.95%). SMS Berjaya Hospital has a solid, well-implemented medical waste management system.